Employees’ Engagement Practices in Spinning Mills - An Empirical Study - Bharathi, N. (Prabandhan: Indian Journal of Management, 2009)
In business, the value of HR function has its impact on higher productivity, enhanced quality, better customer service, good industrial relations and lower cost which are having influence on the profitability of an organizations. Effective HR practices would play important role in achieving all the above said factors. In the present day, HR is viewed as an investment that can lead to further gains. So there is a need to align the human resource practices in such a way to insist on engagement by workers. Such practices can shape the mind of the workers emotionally, which is important fundamentally to drive bottom line success in a company. Hence, the present study focuses on how the employees in spinning mills perceived the factors that have influence on engagement practices.